2021
DOI: 10.1007/s00122-021-03992-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a natural polymorphism in FT-A2 associated with increased number of grains per spike in wheat

Abstract: Key message We discovered a natural FT-A2 allele that increases grain number per spike in both pasta and bread wheat with limited effect on heading time. Abstract Increases in wheat grain yield are necessary to meet future global food demands. A previous study showed that loss-of-function mutations in FLOWERING LOCUS T2 (FT2) increase spikelet number per spike (SNS), an important grain yield component. However, these mutations were also associated with red… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…A similar result has been recently reported for the FT-A2 gene, where the derived A10 allele associated with increases in SNS was found at high frequency in common wheat (~60%) but was almost absent in modern durum wheat commercial varieties (0.7%) [36]. These results suggest that other genes involved in the regulation of spike development may have differential frequencies between common and durum wheat as a result of this putative selection for large grains.…”
Section: Effects Of Different Wapo-a1 Natural Alleles and Their Poten...supporting
confidence: 88%
See 1 more Smart Citation
“…A similar result has been recently reported for the FT-A2 gene, where the derived A10 allele associated with increases in SNS was found at high frequency in common wheat (~60%) but was almost absent in modern durum wheat commercial varieties (0.7%) [36]. These results suggest that other genes involved in the regulation of spike development may have differential frequencies between common and durum wheat as a result of this putative selection for large grains.…”
Section: Effects Of Different Wapo-a1 Natural Alleles and Their Poten...supporting
confidence: 88%
“…The WAPO-A1 H2 haplotype was found in only one accession from Syria in a survey of 364 durum wheat varieties [ 10 ]. Similarly, the FT-A2 A10 allele was found only in three accessions from Oman and Turkey in a survey of 417 durum wheat varieties [ 36 ]. In this study, we show that the transfer of the WAPO-A1 H2 haplotype from common wheat into the tetraploid wheat Kronos was associated with significant increases in SNS and GNS.…”
Section: Discussionmentioning
confidence: 99%
“…As previously proposed 24 , our results imply that WAPO-A1b promotes an increase in sink capacity which may require introgression into high-biomass productive varieties and cultivation under conditions that support high yield potential. The observed trade-offs are not unique to WAPO1 and have been shown in other genes that increase sink capacity such as FT2 59 and FUL2 3 . In rice it has also been reported that Os APO1 increases yield 13 , but that the effect on yield is source dependent 60 and dependent on gene expression levels as described above.…”
Section: Discussionmentioning
confidence: 77%
“…As previously proposed 24 , our results imply that WAPO-A1b promotes an increase in sink capacity which may require introgression into high-biomass productive varieties and cultivation under conditions that support high yield potential. The observed trade-offs are not unique to WAPO1 and have been shown in other genes that increase sink capacity such as FT2 51 and FUL2 3 . In rice it has also been reported that Os APO1 increases yield 13 , but that the effect on yield is source dependent 52 and dependent on gene expression levels as described above.…”
Section: Discussionmentioning
confidence: 77%